9=g/2+6

Simple and best practice solution for 9=g/2+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9=g/2+6 equation:



9=g/2+6
We move all terms to the left:
9-(g/2+6)=0
We get rid of parentheses
-g/2-6+9=0
We multiply all the terms by the denominator
-g-6*2+9*2=0
We add all the numbers together, and all the variables
-1g+6=0
We move all terms containing g to the left, all other terms to the right
-g=-6
g=-6/-1
g=+6

You can always share this solution

See similar equations:

| y-22=-42 | | -x+5/2=9 | | X+8(1-x)=1 | | 4m+9=5m-8/5 | | -36=-9(6+2x) | | 8=f/2+6 | | 54+x=-78 | | 1+2r+6=3 | | y-17=-46 | | 2r/5=3r | | 6x+10/3=5 | | 5x/3+3=8 | | 5x?1=24 | | 5/6+6(x)=7(x)-2/3 | | 6n+5-10n=4n+4-7n | | 9=6x+2+7x | | 8-7y=10 | | ?14=?(?2x+2) | | 4x+(x+5)=25 | | -2(x+4)-7=-15 | | x/6/x/7=7/6 | | X÷4=90-x | | 8=n/3+7 | | 3/2d+18=1d-3 | | 12+6n=4n+6n | | X^2-25=-4x-4 | | 19-x=-11 | | 5x+0.4=5.4 | | 28=y-12 | | 8y+7=15 | | 4(y-2)+11=13 | | 3(6y)-y=75 |

Equations solver categories